Assessment of groundwater suitability for irrigation purposes in the Fritissa region, Moulouya, Morocco - Ben Driss, Moulay Ahmed; Ifliliss, Abdelhadi; Ettazarini, Said; Hahou, Yousef; Boudad, Larbi; El Amrani, Mohamed; Courba, Said (Frontiers in Geochemistry, 2024)
Under arid and semi-arid climate conditions, as is the case in many Moroccan regions, the availability and quality of water are the main keys to the sustainable development of agricultural zones. In the Fritissa region covering Middle Moulouya and a part of Lower Moulouya, North-eastern Morocco, irrigation practices are necessary for agricultural activities, in an environment with significant population growth, and limited water resources. The main aim of this study is to assess the quality of groundwater and its suitability for irrigation purposes, and to determine the possible water-rock interaction processes that influence the groundwater chemistry. The approach is based on the analysis of major ions contents and the calculation of quality indices namely pH, Electrical conductivity (EC), Total Dissolved Solids (TDS), Total Hardness (TH), Sodium Percentage (Na%), Residual Sodium Carbonate (RSC), Sodium Adsorption Ratio (SAR) and Permeability Index (PI) for 94 groundwater samples. Piper classification is used to determine the chemical water facies, while commonly used distribution and geochemical diagrams helped to discuss the possible interaction processes between water and aquifer rocks. The studied groundwater showed varying values for pH (5.8 to 8.8), salinity (367 to 3301 mg/l) and total hardness (15 to 186 mg/l as CaCO3). Ca-Mg-HCO3, Ca-Mg-SO4-Cl, and mixed water facies types are found, while one sample showed Na-K-SO4-Cl facies. The plotting of samples in Gibbs diagrams suggests possible water-rock interactions, that are confirmed by geochemical distribution diagrams. The Wilcox diagram showed that most of the water samples are of excellent to good and good to permissible categories, while the US salinity Hazard diagram revealed low sodium hazard and low, medium and high levels of salinity. Groundwater is suitable for irrigation according to current international standards if some precautions are considered.